Training Report on Climate Risk Management in Agricultural Extension - Sow, Sadibou; Thior, Yakhya El Hadji; Diop, Mbaye; Tall, Thierno Aliou; Seck, Babacar (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
As part of its efforts to integrate the issue of climate change into university curricula, and to accelerate its consideration in decision-making at the level of agricultural producers, the AICCRA (Accelerating the Impact of CGIAR Climate Research for Africa) project, in conjunction with the International Livestock Research Institute (ILRI) and the International Research Institute for Climate and Society (IRI) of the Columbia Climate School, has organized a series of workshops. The first was held in December 2022 at the Fleur de Lys Hotel in Point E - Dakar, and focused on curriculum development. Its aim was to determine the appropriate targets for training in climate risk management in agricultural extension. It also proposed a training curriculum adapted to learners at BAC to BAC+3 levels. The typical model proposed is the advisor and CAR. At the end of the workshop, a roadmap was proposed which would firstly enable us to propose content to reinforce the courses and hold a workshop to train the trainers. Additional materials were implemented, particularly in the areas of livestock breeding and value chains. Other materials were also developed to reinforce the capacities of the RACs. Several structures took part in these workshops. These included : ANCAR, MLouma, Jokolanté, CNCR, ISFAR/UADB, USSEIN, UAMB and RESOP. Following the training of trainers, it was decided to hold pilot training sessions for technical staff in the regions corresponding to the four AICCRA sites, which also have the advantage of covering the following different agro-ecological zones: Méouane in the Niayes zone, Thiel in the sylvopastoral zone, and Kaffrine - in the forest zone.